2011
DOI: 10.1590/s0103-51502011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de um programa de reabilitação pulmonar sobre mecânica respiratória e qualidade de vida de mulheres obesas

Abstract: Efeitos de um programa de reabilitação pulmonar sobre mecânica respiratória e qualidade de vida de mulheres obesas [I] Effects of a pulmonary rehabilitation program over respiratory mechanics and life quality upon obese women [A]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
2
0
3
Order By: Relevance
“…One study performed in 2011 found the efficacy of pulmonary rehabilitation program to promote significant alterations in respiratory mechanics of 20 obese women, indicating an improvement of thoracic mobility 20 , similar to the present study; however, here were evaluated women and men and also compared the values between the genders.…”
Section: Discussionsupporting
confidence: 84%
“…One study performed in 2011 found the efficacy of pulmonary rehabilitation program to promote significant alterations in respiratory mechanics of 20 obese women, indicating an improvement of thoracic mobility 20 , similar to the present study; however, here were evaluated women and men and also compared the values between the genders.…”
Section: Discussionsupporting
confidence: 84%
“…Obese individuals undergoing pulmonary rehabilitation showed an increase in PI max (Δ: −28 cm H 2 O), chest (Δ: 1.4), xiphoid and abdominal amplitudes (Δ: 3 cm) (Costa et al, 2003). Aerobic and resistance exercise increased axillary cirtometry (cm) (Δ: 1.58) and expiratory xiphoid (Δ: 1.68) and PI max (Δ: −8.5 cmH 2 O) (Sonehara et al, 2011). Another study showed an increase in VRI (Δ: 0.32 l), VRE (Δ: 0.21 l) and axillary mobility (Δ: 1.4 cm) (Costa, Forti, Barbalho-Moulim, and Rasera-Junior, 2009).…”
Section: Ca Riskmentioning
confidence: 99%
“…Essas alterações diminuem o movimento torácico e prejudica a ventilação pulmonar. 30,27 Pacientes que ainda não apresentam tórax em tonel com alterações musculares estruturadas se beneficiam integralmente dos exercícios de alongamento e relaxamento muscular. Isto melhora a elasticidade muscular e, assim, permite a incursão funcional mais adequada da musculatura respiratória.…”
Section: Relaxamento Muscularunclassified